Accounting Students on the Role of AI: Future of Accountants - Jefriyanto Jefriyanto; Helga Nuri Honesty; Herlinda Fitri Febriyanti; Rifaldo Rifaldo; Kartika Amalia Arundari; Mohamad Shamil Ulwan (Yayasan Keluarga Guru Mandiri, 2025)
The rapid advancement of technology, particularly artificial intelligence (AI), has profoundly impacted the accounting profession. Despite extensive research examining the effects of technology and AI on accounting practices globally, studies specifically addressing the readiness of accounting students in Indonesia to adapt to AI remain limited. This study explores students' readiness at Universitas Negeri Padang to face the challenges of the Industrial Revolution, particularly concerning AI integration into accounting practices. A quantitative research approach will be employed to achieve this objective, utilizing surveys to gather data from a sample of accounting students. The research framework is built around three main hypotheses. Technological competence positively affects students' accounting competence; The accounting curriculum influences students' accounting competence; and accounting competence positively affects students' readiness to work with AI. The findings of this research are anticipated to provide valuable insights into how educational frameworks can be enhanced to prepare better accounting students for the demands of an AI-driven profession. Ultimately, the study seeks to contribute to improving the accounting curriculum, thereby increasing students' readiness to succeed in an evolving job market.